Endocytotic uptake of FITC-labeled anti-H. pylori egg yolk immunoglobulin Y in Candida yeast for detection of intracellular H. pylori - Saniee, Parastoo; Siavoshi, Farideh (Frontiers in Microbiology, 2015)
Intracellular life of H. pylori inside Candida yeast vacuole describes the establishment of H. pylori in yeast as a pre-adaptation to life in human epithelial cells. IgY-Hp conjugated with fluorescein isothiocyanate (FITC) has been previously used for identification and localization of H. pylori inside the yeast vacuole. Here we examined whether FITC-IgY-Hp internalization into yeast follows the endocytosis pathway in yeast. Fluorescent microscopy was used to examine the entry of FITC-IgY-Hp into Candida yeast cells at different time intervals .The effect of low temperature, H2O2 or acetic acid on the internalization of labeled antibody was also examined. FITC-IgY-Hp internalization initiated within 0-5 min in 5-10% of yeast cells, increased to 20-40% after 30 min-1hr and reached >70% before 2 hr. FITC-IgY-Hp traversed the pores of Candida yeast cell wall, reached the vacuole where it bound with H. pylori antigens. Internalization of FITC-IgY-Hp was inhibited by low temperature, H2O2 or acetic acid. It was concluded that internalization of FITC-IgY-Hp into yeast cell is a vital phenomenon and follows the endocytosis pathway. Furthermore, it was proposed that FITC-IgY-Hp internalization could be recruited for localization and identification of H. pylori inside the vacuole of Candida yeast.